Effects of harvest stages, postharvest pre-treatments and storage duration on the quality and shelf life of minimally processed litchi - Nhleko, Zanele Veronica (My University, 2022)
The most common postharvest limitation of litchi fruit is pericarp browning, which leads to consumer rejection of the solid fruit in the market even when the edible portion is not affected. Previously, sulphur dioxide (SO2) fumigation was used to control the browning and extend shelf life of litchi fruit. However, SO2 fumigation leaves undesirable residues, alters the fruit taste and may results in health hazards for consumers. An alternative method, namely, minimal processing was used to control pericarp browning and curb postharvest losses in litchi. Litchi fruit were harvested at two maturity stages (early harvest; 120 days after full bloom (DAFB), late harvest; 130 DAFB), peeled and immersed for two (2) minutes in three (3) solutions that represented treatments, namely 1) 1% citric acid 2) 1% calcium lactate and 3) a combination of citric acid and calcium lactate both at 1% measure. The untreated arils were dipped in sodium hypochloride (NaOCl) solution for 1 minute and represented the control samples. The treated arils were packed in sterilized clamshell containers and stored at 1±0.5°C and 95% relative humidity for 12 days, then held at 10±0.5°C for 2 days for shelf life study. As a result of the interaction effect of harvest stages and postharvest pre-treatments, least mass loss percentage (1.32%), juice leakage (1.8 ml per 120 g of fruit) and pH (4.18) was observed in litchi arils harvested late and treated with 1% citric acid only under cold storage. Under shelf life study, H2 control samples presented lower mass loss (2.8%) and juice leakage (4.2 ml per 120 g of fruit). At the end of cold storage, litchi arils harvested early and treated with 1% citric acid combined with 1% calcium lactate presented better tissue strength (56.0 N) and radical scavenging activity (36.6 mmol AAE/mL), while those harvested late presented higher ascorbic acid content (72.9 µg/mL), least microbial population and total colour change (3.5). However, at the end of shelf life storage, litchi arils harvested early and treated with 1% citric acid combined with 1% calcium lactate presented lower (3.1) total change in colour. Overall, harvesting the fruit late and treating with citric acid alone or combined with calcium lactate showed the potential of maintaining better aril quality with least microbial population for up to 12 days under 1±0.5°C storage, whereas harvesteing the fruit early and treating with citric acid alone or combined with calcium lactate showed the potential of maintaining better aril quality under shelf life storage. Keywords: Litchi chinesis sonn; calcium lactate; citric acid; maturity; fresh-cut.
Thesis (M.Sc. Agriculture (Horticulture)) -- University of Limpopo, 2022
Keywords: Litchi chinesis sonn; Calcium lactate; Citric acid; Maturity; fresh-cut; Harvesting; Fruit -- Harvesting; Food -- Shelf-life dating; Postharvest diseases and injuries; Citric acid; Litchi chinensis